2016
DOI: 10.1093/hmg/ddw213
|View full text |Cite
|
Sign up to set email alerts
|

Molecular disturbance underlies to arrhythmogenic cardiomyopathy induced by transgene content, age and exercise in a truncated PKP2 mouse model

Abstract: Arrhythmogenic cardiomyopathy (ACM) is a disorder characterized by a progressive ventricular myocardial replacement by fat and fibrosis, which lead to ventricular arrhythmias and sudden cardiac death. Mutations in the desmosomal gene Plakophilin-2 (PKP2) accounts for >40% of all known mutations, generally causing a truncated protein. In a PKP2-truncated mouse model, we hypothesize that content of transgene, endurance training and aging will be determinant in disease progression. In addition, we investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Moreover, in cardiac‐myocyte‐specific VCL knock‐out mice, 2 stages of phenotype were observed: SCD caused by ventricular tachycardia attacked 49% mice younger than 3 months despite well‐preserved systolic cardiac function, while the surviving mice developed dilated cardiomyopathy and died of heart failure around 6 months of age . Similar effects were also observed in heterozygous JUP and truncated PKP2 mice, in which cardiac arrhythmia appeared preceding the structural abnormalities . Interestingly, reduced expression of Nav1.5 in cell membrane also appeared in these models .…”
Section: Our Hypothesismentioning
confidence: 69%
See 2 more Smart Citations
“…Moreover, in cardiac‐myocyte‐specific VCL knock‐out mice, 2 stages of phenotype were observed: SCD caused by ventricular tachycardia attacked 49% mice younger than 3 months despite well‐preserved systolic cardiac function, while the surviving mice developed dilated cardiomyopathy and died of heart failure around 6 months of age . Similar effects were also observed in heterozygous JUP and truncated PKP2 mice, in which cardiac arrhythmia appeared preceding the structural abnormalities . Interestingly, reduced expression of Nav1.5 in cell membrane also appeared in these models .…”
Section: Our Hypothesismentioning
confidence: 69%
“…101 Similar effects were also observed in heterozygous JUP and truncated PKP2 mice, in which cardiac arrhythmia appeared preceding the structural abnormalities. 102,103 Interestingly, reduced expression of Nav1.5 in cell membrane also appeared in these models. [101][102][103] These findings indicate that mutations in connexome can affect ion-channel functions or ID structures, thus disturbing propagation of electrical impulses and causing arrhythmia in the absence of structural abnormalities.…”
Section: Our Hypothesismentioning
confidence: 81%
See 1 more Smart Citation
“…Several mouse models have been developed for Dsg2 [15, 2022, 36], Jup [12, 23, 13, 37], Pkp2 [16, 24, 38], Dsp [17] and Des [39] showing either early embryonic lethality or different cardiac pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…As proof-of-concept, we chose to study ACM, where epidemiological data and animal models have indicated that enhanced mechanical loading, i.e. exercise, can accelerate disease progression in patients (5,(41)(42)(43)(44). To understand the impact of 2D versus 3D culture, we first investigated 2D monolayers of hiPSC-derived cardiomyocytes subjected to mechanical stretch.…”
Section: Dynamic 8x Loading Reveals a Disease Phenotype Based On A Pamentioning
confidence: 99%